L'accompagnement par les pairs au doctorat pour socialiser les femmes au métier de chercheuse - Catherine E. Déri; Cynthia Vincent; Émilie Tremblay-Wragg
Despite progress achieved in academia regarding gender parity, women remain disadvantaged on several fronts. As professors, researchers, and students, they do not benefit from the same opportunities as their male colleagues. In this article, we present results from a case study highlighting peer support between PhD candidates requiring to develop academic writing skills to integrate their field of research. Based on a theoretical framework on the socialization to the scholar profession that was developed by Skakni (2011), we analyze semi-structured interviews conducted with 25 PhD candidates from Canadian universities. The findings reveal that participants prefer to join forces with their equals by joining academic writing groups to normalize their challenges faced in academic settings. Moreover, they seem to value the support they receive from their peers, as much as the support they offer to their female counterparts. As a consequence, professional and personal collaborations emerge, through the establishment of a network of novice scholars promoting solidarity, instead of the competition usually observed in graduate studies. We then discuss the feminine perspective on this culture of competition and the gender differences leading to a disparity in socialization requirements in academia. Finally, we offer suggestions for further exploration of student-led actions, in conjunction with institutional support, to optimize the socialization of female PhD candidates, and by the same token, their insertion into the scholar profession.